The Next Era for Earth Observation Spacecraft: An Overview of CogniSAT-6 - David Rijlaarsdam; Tom Hendrix; Pablo T. Toledano Gonzalez; Alberto Velasco-Mata; Leonie Buckley; Juan Puig Miquel; Oriol Aragon Casaled; Aubrey Dunne (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Earth Observation (EO) spacecraft plays a pivotal role in various critical applications impacting life on Earth. Historically, these systems have adhered to conventional operational paradigms, namely the “mow-the-lawn” and “bent pipe” approaches. In these paradigms, operational schedules are formulated on the ground and subsequently uploaded to the spacecraft for execution. Execution involves either systematically acquiring vast amounts of data (mow-the-lawn) or targeting specific areas of interest as defined by end users or operators. We aim to depart from these traditional methodologies by integrating onboard artificial intelligence, near real-time communication, and new observing strategies in one system called CogniSAT-6. These innovations will amplify the amount, speed, and quality of the information yielded by such a system by up to an order of magnitude. This article provides an overview of the current state of the art in autonomous EO spacecraft and the application of onboard processing in EO spacecraft. An overview is given of the CogniSAT-6 mission, its concept of operations, system architecture, and data processing design. In addition, the first results of our in-orbit functional tests are presented. Since we believe that the technology presented here will have a significant impact on society, an ethical framework for such systems is presented. Finally, the benefits of the technology and implications for EO systems going forward are discussed.